Sex-specific associations of fat and lean indices with vertebral fractures - Yen-Huai Lin; Michael Mu Huo Teng (Scientific Reports)
Abstract The relationship between body composition and fracture sites is complex. Previous studies have reported that a site-dependent relationship between body mass index (BMI) and fractures in postmenopausal women and older men. This study aimed to investigate sex-specific associations of fat and lean indices with vertebral fractures. This cross-sectional study included 1,479 participants, with body composition assessed using dual-energy X-ray absorptiometry. Fat indices included BMI, body fat percentage, and waist circumference, whereas the lean index was represented by appendicular lean mass (ALM)/height². Prevalent vertebral fractures were identified through radiographic confirmation. When both fat and lean indices simultaneously were considered, BMI (odds ratio [OR], 1.15; 95% confidence interval [CI] 1.08–1.22), body fat percentage (OR, 1.06; 95% CI 1.02–1.10), and waist circumference (OR, 1.06; 95% CI, 1.03–1.08) were significantly associated with vertebral fractures in postmenopausal women, whereas ALM/height² did not show such an association. In contrast, for men aged ≥ 50 years, ALM/height² was significantly associated with vertebral fractures, whereas fat indices showed no such an association. Furthermore, a significant interaction between ALM/height² and sex was observed. Fat indices were predominantly associated with vertebral fractures in women, whereas the lean index was more strongly associated with vertebral fractures in men. These findings highlight a sex-specific association between body composition and vertebral fractures.